Safety of the Pipeline Embolization Device in Treatment of Posterior Circulation Aneurysms - Phillips , T.J.; Wenderoth, J.D.; Phatouros, C.C.; Rice, H.; Singh, T.P.; Devilliers, L.; Wycoco, V.; Meckel, S.; McAuliffe, W. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: The published results of treating internal carotid artery aneurysms with the PED do not necessarily apply to its use in the posterior circulation because disabling brain stem infarcts can be caused by occlusion of a single perforator. In this multicenter study, we assessed the safety of PED placement in the posterior circulation. MATERIALS AND METHODS: A prospective case registry was maintained of all posterior circulation aneurysms treated with PEDs at 3 Australian neurointerventional centers during a 27-month period. The objective was to assess the complications and aneurysm occlusion rates associated with posterior circulation PEDs. RESULTS: Thirty-two posterior circulation aneurysms were treated in 32 patients. No deaths or poor neurologic outcomes occurred. Perforator territory infarctions occurred in 3 (14%) of the 21 patients with basilar artery aneurysms, and in all 3, a single PED was used. Two asymptomatic intracranial hematomas were recorded. No aneurysm rupture or PED thrombosis was encountered. The overall rate of permanent neurologic complications was 9.4% (3/32); all 3 patients had very mild residual symptoms and a good clinical outcome. Aneurysm occlusion was demonstrated in 85% of patients with >6 months of follow-up and 96% of patients with >1 year of follow-up. CONCLUSIONS: The PED is effective in the treatment of posterior circulation aneurysms that are otherwise difficult or impossible to treat with standard endovascular or surgical techniques, and its safety is similar to that of stent-assisted coiling techniques. A higher clinical perforator infarction rate may be associated with basilar artery PEDs relative to the internal carotid artery. mRSmodified Rankin ScalePEDPipeline Embolization DeviceSFDSilk flow diverterTGATherapeutic Goods AssociationWFNSWorld Federation of Neurological Surgeons